2012
DOI: 10.1111/j.1937-5956.2012.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sales Forecast Model for Short‐Life‐Cycle Products: New Releases at Blockbuster

Abstract: We develop, in this article, a sales model for movie and game products at Blockbuster. The model assumes that there are three sales components: the first is from consumers who have already committed to purchasing (or renting) a product (e.g., based on promotion of, or exposure to, the product prior to its launch); the second comes from consumers who are potential buyers of the product; and the third comes from either a networking effect on closely tied (as in a social group) potential buyers from previous buye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Chung () and Chung et al. () tested this model against the actual demand for 352 titles and found it to be remarkably accurate (the average R2 is 0.96). Hence, we assume that each title's revenue potential is known and is an input to the current study.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Chung () and Chung et al. () tested this model against the actual demand for 352 titles and found it to be remarkably accurate (the average R2 is 0.96). Hence, we assume that each title's revenue potential is known and is an input to the current study.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Casey et al (2012) developed a sales model of movie and game products at Blockbuster company [2]. They assumed that it contains three sales components: consumers who have already bought or rented the products, consumers who are going to buy or rent the products and the networking effect on closely linked potential buyers from previous buyers or re-rents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that new product diffusion was not be affected by persuasive advertisement in the decision-making stage. Chung et al [5] provided a sales forecast model for short-lifecycle products, such as movies and games. Van Den Bulte and Joshi [18] discussed the role of influentials and imitators in the diffusion of new products.…”
Section: Product Diffusion Modelmentioning
confidence: 99%
“…The Bass model discusses at length the impact of the dynamic changes of innovators and imitators on the product sales. Based on the theoretical framework of the Bass model, a large number of product diffusion models are directly divided buyers, then analyze the changes of behaviors of these buyers in the decisionmaking process, and forecast product sales via these changes [4][5][6][7]. Although these models are effective for forecasting product sales, these models only present the changes of individual behaviors in the decision-making stage and fail to reveal how those buyers are formed.…”
Section: Introductionmentioning
confidence: 99%